Trade, value chains, and rent distribution with foreign exchange controls: Coffee exports in Ethiopia - Tamru, Seneshaw; Minten, Bart; Swinnen, Johan (International Food Policy Research Institute, 2019)
Exchange rate policies can have important implications on incentives for export agriculture. However, their effects are often not well understood. We study the issue of foreign exchange controls and pricing in the value chain for Ethiopia’s coffee - its most important export crop. Relying on unique pricing and cost data, we find that coffee exporters are willing to incur losses during exporting by offering high prices for coffee locally in order to access scarce foreign exchange. The losses in export markets are then more than recovered in importing, indicating rents - import parity prices are significantly lower than the prices charged for imported goods, so that profits on imports are much higher than the losses incurred in exporting. We further show that the high coffee wholesale prices are transmitted to farmers, so that they benefit from the rents downstream. These results suggest that a better exchange rate alignment to reduce the overvaluation of the local currency in this case would have a lower impact on export crop producer prices than typically is anticipated.